2019
DOI: 10.1002/naaq.10104
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance of Atlantic Salmon Smolts Fed Diets Containing Heterotrophic Algal Biomass as Replacement of Fish Oil

Abstract: One of the most widely cultured finfish in the world is the Atlantic Salmon Salmo salar, with over 2 million metric tons produced per year. Atlantic Salmon fillets are widely accepted by consumers as a source of long‐chain omega‐3 fatty acids, particularly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). As feed producers shift from using marine ingredients to more terrestrial ingredients, producers need to monitor the fatty acid profiles of the fillets. Juvenile Atlantic Salmon (~280 g) were fed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…This demonstrates that Pav459 could be included in the feeds of Atlantic salmon at up to 20% of the diet without compromising growth and feed utilization parameters. The results of the present study are similar to other feeding trial studies in which the authors did not detect any significant effects on growth parameters when FM was partially replaced by different strains of AB in Atlantic salmon diets [30,31], hybrid striped bass diets [32], European seabass [33], and shrimp diets [34], just to mention a few. Although immunology, lipid oxidation, goblet cells, mucus production, and the microbiome were not a focus of this study, other studies that included microalgal biomass in feeds in aquaculture revealed positive results in enhancing immune response [35,36], decreasing nitric oxide [37], increasing goblet cell density in the anterior intestine [38], modulating mucosal immune function, and increasing microbiome diversity indices for microbial communities in the gut of fish fed diets with PUFA-rich microalgae compared with controls [36].…”
Section: Discussionsupporting
confidence: 90%
“…This demonstrates that Pav459 could be included in the feeds of Atlantic salmon at up to 20% of the diet without compromising growth and feed utilization parameters. The results of the present study are similar to other feeding trial studies in which the authors did not detect any significant effects on growth parameters when FM was partially replaced by different strains of AB in Atlantic salmon diets [30,31], hybrid striped bass diets [32], European seabass [33], and shrimp diets [34], just to mention a few. Although immunology, lipid oxidation, goblet cells, mucus production, and the microbiome were not a focus of this study, other studies that included microalgal biomass in feeds in aquaculture revealed positive results in enhancing immune response [35,36], decreasing nitric oxide [37], increasing goblet cell density in the anterior intestine [38], modulating mucosal immune function, and increasing microbiome diversity indices for microbial communities in the gut of fish fed diets with PUFA-rich microalgae compared with controls [36].…”
Section: Discussionsupporting
confidence: 90%